Heat-treated CNC/PVA composite from natural fibre for wax removal of batik wastewater treatment - Sulaiman, Sarina; Pauzi, S. N.; Rahim, R.; Othman, Maizatulnisa; Jan, H. A; Mel, Maizirwan (Penerbit Akademia Baru, 2019)
Cellulose Nanocrystals (CNCs) have significant properties such as low density, high specific resistance, excellent mechanical properties, biodegradability, low-cost, low abrasive nature, and reactive surface for easy modification. Water contamination from various sources has become a serious problem in recent years. Hence, this study will serve the good application of composite nanocellulose in treating the wax from batik wastewater which needs proper treatment before releasing into the environment. This study also was aimed to synthesize CNCs/PVA composite from coconut fibre and used as adsorbent for the removal of wax from batik industry. The adsorption process was optimized based on parameters such as CNCs dosage and contact time. CNCs/PVA composites were prepared by constant mixing of CNCs suspension in PVA solution at 50°C for 1 hour, dried at 60°C overnight and heat treated at 190°C for 1 hour. Design of Experiments (DOE) was used to study the effects of CNCs dosage to PVA polymer (1-6 %v/w), contact time (15 min to 180 min) at a constant temperature and agitation rate of 48°C and 180 rpm respectively. The highest percentage of wax removal recorded was 50.23% at the optimal conditions of 6 %v/w of CNCs dosage at 180 min. By using natural wastes, the cost of pre-treatment process can be reduced, and this method is much simpler than other conventional methods. Besides, the conversion of the waste to a useful adsorbent also indirectly helps in minimizing the solid wastes.